Respuesta :

Answer:

The simplified expression is   22 x   + 8 y  + 12 = 0

Step-by-step explanation:

Here, the given expression is :  - 6x =  12 + 8y + 16 x

Like Terms:   The terms which have the same coefficient variable in any given expression are called Like Terms.

In the given expression the only pair of like terms is (-6 x, and 16 x)

Solving the given expression , we get:

- 6x =  12 + 8y + 16 x

⇒12 + 8y + (16 x   + 6 x)  = 0

or,  12 + 8 y + 22 x = 0

Hence, the simplified expression is   22x   +8y  + 12 = 0